Kepemimpinan Kepala Sekolah dalam Membina dan Meningkatkan Profesionalitas Pendidikan Agama Islam - J, Fitria (Journal of Innovation in Teaching and Instructional Media, 2021)
This study aims to determine the principal's leadership as educational supervisors in fostering and improving the professionalism of Islamic Religious Education teachers at SD IT Robbani Indralya Ogan Ilir, South Sumatra. This research uses a descriptive qualitative research approach. In this study, the data source or object of this research was the principal and teachers at SD IT Robbani Indralaya Ogan Ilir, South Sumatra. The data was collected using observation, interview, and documentation techniques. Data analysis using the Milles and Huberman model which consists of data reduction, data display, verification, and measuring the level of data credibility using data source triangulation techniques. The results showed that the leadership of the Principal of SD IT Robbani Indralaya Ogan Ilir South Sumatra was included in the open leadership category. The professionalism of Islamic Religious Education Teachers at SD IT Robbani Indralaya is quite good, this is shown by the fulfillment of several competency standards such as pedagogical competence, personality competence, social competence, and professional competence.